Pelatihan dan Pendampingan Proses Pembuatan Regulasi Desa di Desa Bonyoh Kecamatan Kintamani - Suastika, I Nengah (JURNAL WIDYA LAKSANA, 2020)
The main objective of the Training and Assistance for village development in Bonyoh, Kintamani Subdistrict is to (1) increase the knowledge and skills of the village head, village apparatus and the Village Consultative Body in making Village Regulations, (2) improve the knowledge and skills of the village head, village apparatus and the Agency Village Consultation in making Village Head Regulations, and (3) improving the knowledge and skills of village heads, village officials and the Village Consultative Body in making Joint Village Head Regulations.Training and Assistance for Making Village Regulation in Bonyoh Village, Kintamani District will be conducted using two synergistic-based methods, namely: training methods and mentoring methods. This training and assistance in making village regulations increases the knowledge and skills of the Village Head and the Village Consultative Body in making village regulations, village head regulations and regulations with village heads. The stages of making village regulations begin with the making of village regulations making, the drafting of village regulations by the Village Head or the Village Consultative Body, then a joint discussion is held between the village head and the Village Consultative Body, the establishment of village regulations, the dissemination of village complaints and discussion of the village.